The Systematic Status and Biology of Telmatobius montanus Lataste (Amphibia, Leptodactylidae) - Cei, José Miguel Alfredo María (1965)
The poorly known Telmatobius montanus was rediscovered in the high Andean mountains between Mendoza and Talca on the Argentinian- Chilean frontier. Morphological characters of the adults and tadpoles are described. There is convergence in male secondary sex characters toward the leptodactylid frogs of the genus Eupsophus (nodosus group).